The Impact of School Environment on Student Character Development in Physical Education at Nusa Alam School, Mataram, NTB - Khaerul Anam (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2023)
The school environment is important in shaping the character of its students, and this is especially true for a subject like physical education. At the Nusa Alam School located in Mataram, NTB, the influence of the school environment on character building in the context of physical education is noteworthy. This study explores this influence, targeting students in Nusa Alam. Using a mixed methods approach that combines observation, questionnaires, and in-depth interviews, this study uncovered a strong positive correlation between school surroundings and students' character development during physical education sessions. This finding underlies the importance of creating a conducive learning atmosphere in schools, the pressure of the role of educators and the environment in shaping student character.